2012
DOI: 10.1578/am.38.4.2012.402
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure in the Hindgut of Wild and Captive Dugongs (Dugong dugon)

Abstract: Dugongs (Dugong dugon) are marine mammals that obtain nutrients through hindgut fermentation of seagrass, however, the microbes responsible have not been identified. This study used denaturing gradient gel electrophoresis (DGGE) and 454-pyrosequencing to profile hindgut bacterial communities in wild dugongs. Faecal samples obtained from 32 wild dugongs representing four size/maturity classes, and two captive dugongs fed on cos lettuce were screened using DGGE. Partial 16S rRNA gene profiles of hindgut bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…. The closest sequence similarity matches using the blast algorithm against the NCBI GenBank and Greengene databases and wild dugong amplicon sequence data set (Eigeland et al ., ) are contained in the Supporting Information, Table S1. Core OTUs that could be classified to the level of genus included Adlercreutzia, Bacteriodes, Butyrivibrio , Caloramator, Cellulosilyticum, Clostridium , Eubacterium, Ruminococcus and Sedimentibacter .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. The closest sequence similarity matches using the blast algorithm against the NCBI GenBank and Greengene databases and wild dugong amplicon sequence data set (Eigeland et al ., ) are contained in the Supporting Information, Table S1. Core OTUs that could be classified to the level of genus included Adlercreutzia, Bacteriodes, Butyrivibrio , Caloramator, Cellulosilyticum, Clostridium , Eubacterium, Ruminococcus and Sedimentibacter .…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial phyla found in the manatees of this study were similar to those that dominate the hindgut flora of the related wild dugong in eastern Australia (Eigeland et al ., ) with Firmicutes (76% of flora) and Bacteroidetes (20%) being dominant, and Actinobacteria and Proteobacteria being the next most prevalent phyla. Further, from six bacterial phyla identified in a single captive dugong held in Japan (Tsukinowa et al ., ), a similar distribution was observed: Firmicutes 83.1%, Bacteroidetes 15%, with the remaining phyla ( Verrucomicrobia , Actinobacteria , Lentisphaerae and Proteobacteria) at < 1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cDNA was then used as template for the production of 16S rRNA gene amplicons for pyrosequencing (see Supplementary Material 8 for detailed PCR protocol). Sequence data were processed, clustered into operational taxonomic units at the 97% identity level and classified as described previously (Eigeland et al, 2012;Gulino et al, 2013). All data processing was performed in QIIME 1.5.0 (Caporaso et al, 2010).…”
Section: Amplicon Pyrosequencingmentioning
confidence: 99%
“…Liu D et al 14 used 16S rDNA PCR-DGGE methodology to provide a profile of the dominant gut microbiota of Chinese neonates, but the PCR-DGGE method used may limit the generalizability of their results. It has been previously demonstrated that species richness and diversity were higher for the samples analyzed by 454-pyrosequencing than DGGE15.…”
mentioning
confidence: 93%